Integration of spatial analysis and an agent-based model into evacuation management for shelter assignment and routing. Issue 2 (2nd July 2016) - Liu, Xuefen; Lim, Samsung
Abstract: Evacuation planning is a complex and challenging task as it requires an integrated approach to heterogeneous spatial datasets, including population, road network and facilities. Evacuation management of emergency situations is often based on delineation of evacuation circumstances and spatial analyses of the datasets. A practical evacuation management system would be a system that provides an easy configuration to evacuation managers who may not have full knowledge of spatial analysis functionality of geographic information system (GIS) software but need to understand the emergency situation promptly and provide decisive instructions which can be fulfilled when they manage the datasets and develop new workflows in various scenarios. An agent-based simulation approach is capable of demonstrating the spatio-temporal aspect of complex dynamic systems. Spatial analysis toolkits embedded in GIS software and open-source software are utilised in order to demonstrate the feasibility of enabling users to manage spatial data and customise the spatial analysis by combining common data analysis tools to meet their requirements in evacuation planning from both spatial and temporal perspectives. This paper proposes a shelter assignment and routing strategy for evacuating households at the 2011 Brisbane flood event as a scenario-based case study. The result shows that communities located in the east and west of Brisbane are scarcely covered by existing shelters. Furthermore, an agent-based simulation for households located in the service areas of three shelters indicates that the corresponding clearance time is 50 minutes. It is envisaged that this study can assist urban planners and emergency managers in developing an effective evacuation plan for a flood disaster in Brisbane.